Предмет: Математика,
автор: Изобелль
упростить выражение b/a-b:(a/a-b - a+b/a)
Ответы
Автор ответа:
0
b/a-b:(a/a-b - a+b/a)
1) (a/a-b - a+b/a)=a^2-(a+b)(a-b)/a(a-b)=a^2-(a^2-b^2)/a(a-b)=a^2-a^2+b^2/a(a-b)=b^2/a(a-b)
2)b/a-b * a(a-b)/b^2= a/b
1) (a/a-b - a+b/a)=a^2-(a+b)(a-b)/a(a-b)=a^2-(a^2-b^2)/a(a-b)=a^2-a^2+b^2/a(a-b)=b^2/a(a-b)
2)b/a-b * a(a-b)/b^2= a/b
Похожие вопросы
Предмет: Алгебра,
автор: mashabalukova0613
Предмет: Химия,
автор: armyblinki
Предмет: Математика,
автор: ivancykdiana
Предмет: Биология,
автор: 1а1а1а1а1а